2018
DOI: 10.1371/journal.pone.0193342
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl sulfate, indoxyl sulfate and p-cresyl sulfate decrease glutathione level to render cells vulnerable to oxidative stress in renal tubular cells

Abstract: In chronic kidney disease patients, oxidative stress is generally associated with disease progression and pathogenesis of its comorbidities. Phenyl sulfate is a protein-bound uremic solute, which accumulates in chronic kidney disease patients, but little is known about its nature. Although many reports revealed that protein-bound uremic solutes induce reactive oxygen species production, the effects of these solutes on anti-oxidant level have not been well studied. Therefore, we examined the effects of protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…2d, PS was toxic to differentiated podocytes from 30 μM and significant cell toxicity was seen at concentrations from 100 μM. We also measured the effect of PS on glutathione levels, as it was reported PS decreases glutathione levels, rendering the cells vulnerable to oxidative stress 14 . Glutathione levels in differentiated podocytes exposed to PS (30 μM) decreased and significant at 100 μM (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2d, PS was toxic to differentiated podocytes from 30 μM and significant cell toxicity was seen at concentrations from 100 μM. We also measured the effect of PS on glutathione levels, as it was reported PS decreases glutathione levels, rendering the cells vulnerable to oxidative stress 14 . Glutathione levels in differentiated podocytes exposed to PS (30 μM) decreased and significant at 100 μM (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Differentiated HUPEC 13 were cultured in RPMI1640 supplemented with 2% FBS and plated at 0.5 × 10 4 cells/0.5 mL assay medium per well in 96-well collagen-coated culture plates and modified with the relevant culture condition, as reported 14 . After each compound was applied at the final concentration indicated, differentiated podocytes were cultured for 72 h and cell viability was measured by Cell Count Regent SF (Nacalai Tesque, Kyoto, Japan) as previously reported 17 .…”
Section: Methodsmentioning
confidence: 99%
“…In the periphery, PCS has effects on oxidative stress, inflammation, mitochondrial activity, vascular function, and cell viability [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In the prefrontal cortical tissues we found that PCS increased the expression and activities of redox-sensitive and proinflammatory molecules, such as IL-1β, JNK, p38, p65, NF-κB, and AP-1, along with a reduction in circulating BDNF and serotonin as well as an increase in corticosterone.…”
Section: Discussionmentioning
confidence: 99%
“…PCS displays diverse biological activities. Accumulating evidence has shown that PCS causes cell death and dysfunction centered around oxidative stress, inflammation, impairment of mitochondrial dynamics, and vascular disruption [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Thus, both the causative and pathogenic effects of PCS in CNS diseases are highly proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome has emerged as a pivotal actor and therapeutic target in a variety of diseases, now including CKD. 7,14,17 The notion of "drugging the microbiome" was recently developed as a proof of concept in the context of atherosclerosis by using an approach based on selective inhibition of the microbial pathway generating TMAO. 18 The work of Kikuchi et al further expands this proof of concept, demonstrating that inhibiting the PS synthetic pathway results in reductions in PS and creatinine levels in a mouse model, suggesting potential renoprotection without significantly altering microbial taxonomic balance.…”
Section: How Does This Study Compare With Prior Studies?mentioning
confidence: 99%